2010
DOI: 10.1182/blood-2010-01-266072
|View full text |Cite
|
Sign up to set email alerts
|

A chemotactic gradient sequestered on endothelial heparan sulfate induces directional intraluminal crawling of neutrophils

Abstract: During infection, chemokines sequestered on endothelium induce recruitment of circulating leukocytes into the tissue where they chemotax along chemokine gradients toward the afflicted site. The aim of this in vivo study was to determine whether a chemokine gradient was formed intravascularly and influenced intraluminal neutrophil crawling and transmigration. A chemokine gradient was induced by placing a macrophage inflammatory protein-2 (MIP-2)-containing (CXCL2) gel on the cremaster muscle of anesthetized wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
183
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(191 citation statements)
references
References 42 publications
7
183
0
1
Order By: Relevance
“…Neutrophils move along an IL-8 gradient. 94,95 IL-8 also activates neutrophils, increasing surface expression and binding activity of MAC1 (a complement receptor). 96,97 In patients with dermatitis herpetiformis, serum IL-8 is elevated following the immune response to dietary gluten in the small bowel.…”
Section: Dapsonementioning
confidence: 99%
“…Neutrophils move along an IL-8 gradient. 94,95 IL-8 also activates neutrophils, increasing surface expression and binding activity of MAC1 (a complement receptor). 96,97 In patients with dermatitis herpetiformis, serum IL-8 is elevated following the immune response to dietary gluten in the small bowel.…”
Section: Dapsonementioning
confidence: 99%
“…Indeed, this chemotactic gradient is sequestered on endothelial HS and provides directional cues to crawling neutrophils, which follow this gradient to optimal transmigration sites close to the origin of the infection (Massena S. et al, 2010). However, whether haptotactic gradients can be established by all chemokines remains unclear, since different chemokines have diverse affinity to HS (Lindhal U., Kjellén L., 1991;Lindhal U., 2007).…”
Section: Neutrophil Crawlingmentioning
confidence: 99%
“…It is generally believed that increased permeability supports chemokine influx into the vessels and one hypothesis is that the increase in vascular permeability during inflammation grants the paracellular transport of chemokines for rapid presentation to intravascular leukocytes, guiding them out to the afflicted area in the tissue. A recent study using intravital spinning-disk confocal microscopy in anesthetized mice revealed that chemokines added extravascularly became accumulated intra-luminally at endothelial cell junctions (Massena S. et al, 2010). High junctional sequestration of chemokines suggests that chemokines are transported either paracellularly into blood vessels or longitudinally on the apical endothelial cell membrane towards junctions after being transcytosed.…”
Section: Intravascular Chemokine Presentation To Rolling Leukocytesmentioning
confidence: 99%
See 2 more Smart Citations